Ethics in Public Policy and Management 2015
DOI: 10.4324/9781315856865-12
|View full text |Cite
|
Sign up to set email alerts
|

Researching and Improving The Effectiveness of Ethics Training

Abstract: This chapter starts out with a review of existing evaluation research on ethics training. This not only generates some useful insights but also reveals some important methodological and theoretical problems. As for the latter, specifications of the main variables are often vague, resulting in equally vague hypotheses, difficult to falsify or corroborate. The chapter hopes to address these concerns by proposing a conceptualization of both the independent variable, 'ethics training', and dependent variable, 'eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, no claim is made that the ethical quotient is an accurate or distinguishing measure between individuals or organizations on their level of ethical competence. Furthermore, based on another ethical competence framework from previous studies, Table 3 shows the description of AI and EI elements consisting in the framework [22]- [24]. Therefore, the previous study and Table 3 showed a lack of an ethical competence model or framework that blends AI and EI skills.…”
Section: Development Of Ethical Competence Modelmentioning
confidence: 96%
“…However, no claim is made that the ethical quotient is an accurate or distinguishing measure between individuals or organizations on their level of ethical competence. Furthermore, based on another ethical competence framework from previous studies, Table 3 shows the description of AI and EI elements consisting in the framework [22]- [24]. Therefore, the previous study and Table 3 showed a lack of an ethical competence model or framework that blends AI and EI skills.…”
Section: Development Of Ethical Competence Modelmentioning
confidence: 96%
“…Our approach is innovative insofar as we stipulate that approaches that support the achievement of one type of learning outcome of RCR may not be as helpful in achieving other learning outcomes and vice versa. Drawing on a recent taxonomy of learning outcomes in the moral/ethical domain (Maesschalck and De Schrijver, 2015), a synthesis of the abilities underlying moral agency (Tanner and Christen, 2014), and a taxonomy of learning objectives for RCR (Antes and DuBois, 2014), we distinguish five types of learning outcomes: & Knowledge: Ability to understand, remember, and recall concepts, facts, and procedures related to RCR. & Attitude: Endorsement and expression of beliefs, motivations, and attitudes that reflect research integrity and a willingness to exercise research in a responsible manner, including the endorsement of specific norms and standards.…”
Section: Introductionmentioning
confidence: 99%
“…Integrity training is one of the most popular instruments as well as a common method for many organisations to promote integrity among their employees (Maesschalck & De Schrijver, 2015). As with ISAI, state auditing standards require that auditors maintain their competence through continuous training of at least 80 hours spread over every two years.…”
Section: Training In Ethics Is It Worth Doing?mentioning
confidence: 99%